Facilitation skills for team leaders - Hackett, Donald (Crisp Pub. Menlo ParkUS, 1993)
Explains the concept of facilitation - looks at the facilitator's role and shows how facilitation differs from training and presenting. Presents a number of facilitation skills including; questions and questioning; the six-step problem-solving process; running a team meeting; and achieving concensus. Identifies essential facilitation tools, namely, the flow chart, brainstorming, cause-and-effect diagrams, and Pareto diagrams; and explains how to construct /conduct them. \n \n